Transformasi Pembelajaran Sastra Arab Di Era Digital: Pengembangan Media Interaktif Berbasis Proyek Untuk Analisis Cerpen Arab - Dyah Adila Perdana (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Digital transformation has brought significant changes to the field of education, including Arabic literature learning in higher education. However, Arabic literature instruction is still frequently dominated by conventional teacher-centered approaches that are less capable of accommodating the characteristics of digital-native students. This condition affects students’ engagement in the learning process and limits their ability to critically and deeply analyze literary works. This article aims to examine the development of project-based interactive media as an innovative learning alternative for Arabic short story analysis in the digital era. The study employed a Research and Development (R&D) approach through the stages of needs analysis, media design, product development, validation, and evaluation. The findings indicate that project-based interactive media support a more active, interactive, and student-centered learning environment through the integration of multimedia elements, literary analysis activities, and project-based tasks. The implementation of such media has the potential to enhance students’ literary analysis skills, including understanding intrinsic literary elements, critical thinking, literary interpretation, academic communication, collaboration, creativity, and digital literacy. Nevertheless, the implementation of project-based interactive media still faces several challenges, such as varying levels of digital literacy, technological infrastructure limitations, and the complexity of project-based learning management. Therefore, support from institutions, lecturers, and students is essential to optimize the use of digital media in Arabic literature learning. Project-based interactive media can serve as a relevant solution to support the transformation of Arabic literature learning toward a more effective, innovative, and twenty-first-century-oriented educational practice.